IDENTIFIKASI BANGUNAN YANG BERADA DALAM KAWASAN SEMPADAN SUNGAI MUSI (BANGUNAN STATUS QUO) KOTA PALEMBANG - Putri, Debi Nadia; Sastra, Ahmad Ridho (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
ABSTRACT Palembang City is a city located in South Sumatra Province and has the status as the capital of South Sumatra Province. Palembang City is geographically crossed by the Musi River. The Musi River is iconic in the city of Palembang. This is marked by the direction of development of the Musi River bank area as a tourism area which is regulated in Palembang City Regional Regulation Number 15 of 2012 concerning Regional Spatial Planning (RTRW) of Palembang City for 2012-2032. Along with the development of Palembang City which is marked by increasing development around the banks of the Musi River, areas in the Musi Riverbank area have been used as residences or settlements by residents. This is certainly in conflict with the Regulation of the Minister of Public Works and Public Housing Number 28/PRT/M/2015 of 2015 concerning the Determination of River Border Lines and Lake Border Lines. Article 15 paragraph 1 states that buildings located on the riverbank are declared in